Analisis Daya Dukung Air Untuk Kebutuhan Air Bersih Domestik di Kecamatan Gianyar dan Ubud, Kabupaten Gianyar - NAPITU, DEBORA TIENCICIA; WIYANTI, WIYANTI; DIARA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.2, April 2018, 2018)
Analysis of Water Carrying Capacity For Domestic Clean Water Needs in Gianyar and Ubud District of Gianyar Regency Water is the main needs used sustainably. The needs of water always increases in line with the growth of the human population. The increase of water needs for domestic compels a region to maintain the availability of water in order to support the clean water needs. The aim of this study was to found out the water carrying capacity to fulfill the need of clean water of domestic in Gianyar and Ubud sub-districts, Gianyar regency. The research was done using descriptive quantitative method and to determine the number of respondent using stratified random sampling method. The water needs for domestic in Gianyar sub-district is 2,671,391.2 m3year-1 and the potency of water availability was calculated based on the surface water is 513,232.9193 m3year-1; groundwater recharge is 653,205.5337 m3 year-1; and the groundwater basin is 22,000,000.16 m3 year-1. The water needs for domestic in Ubud sub-district is 2,111,598 m3 year-1 and the potency of water availability was calculated based on the surface water is 476,395.4871 m3 year-1; groundwater recharge is 582,261.1509 m3 year-1; and the groundwater basin is 18,000,000.99 m3 year-1. Carrying capacity index of surface water in Gianyar sub-district is 0.19; groundwater recharge is 0.24 and the groundwater basin is 8.23. Carrying capacity index of surface water in Ubud sub-district is 0.22; groundwater recharge is 0.27; and the groundwater basin is 8.52. Based on the analysis, it was found that the status of surface water and groundwater recharge carrying capacity in Gianyar and Ubud sub-district was deficit (water supply < water demand), however carrying capacity of groundwater basin was surplus (water supply > water demand).